The Sound of a Person The Sound of a Person: A Music-Cognitive Study in the Finisterre Range in Papua New Guinea. - Ammann, Raymond; Keck, Verena; Wassmann, Jürg (Oceania, 2013)
Konggap, sung melodic motifs that last only a few seconds embody the acoustic representation of a person among the Yupno people of Papua New Guinea and are a unique phenomenon in the Pacific. The konggap forms a very complex system of personal identification and expression of social relationships; at the same time it connects the singer to the ancestral world. Every person in Yupno society possesses his or her own konggap, and Yupno people are able to identify a large number of konggap, some men even up to three hundred. Nobody would sing his or her own konggap during the day. When crossing Yupno land, a person has to sing the konggap of the respective landowner to identify himself as an insider, a local person − unlike strangers (and possible enemies) who remain silent. But at nightly dances each dancer sings his own konggap and during mourning at funerals groups of women simultaneously sing the konggap of the deceased person. An interdisciplinary ethnographic-musicological-cognitive fieldwork study was conducted in order to find out how it is possible that the Yupno are able to identify and distinguish between this staggering amount of very short sung motifs.